IN THE FIELD OF CYBER-SECURITY AN INTRUSION DETECTION SYSTEM BASED ON HONEYPOT TECHNOLOGY (Conferencea, 2022)
Day by day, more and more people are using internet all over the world. It is becoming a part of everyone’s life. People are checking their e-mails, surfing over internet, purchasing goods, playing online games, paying bills on the internet etc. However, while performing all these things, how many people know about security? Do they know the risk of being attacked, infecting by malicious software? Even some of the malicious software are spreading over network to create more threats by users. How many users are aware of that their computer may be used as zombie computers to target other victim systems? As technology is growing rapidly, newer attacks are appearing. Security is a key point to get over all these problems. In this thesis, we will make a real life scenario, using honeypots. Honeypot is a well designed system that attracts hackers into it. By luring the hacker into the system, it is possible to monitor the processes that are started and running on the system by hacker. In other words, honeypot is a trap machine which looks like a real system in order to attract the attacker. The aim of the honeypot is analyzing, understanding, watching and tracking hacker’s behaviours in order to create more secure systems. Honeypot is great way to improve network security administrators’ knowledge and learn how to get information from a victim system using forensic tools. Honeypot is also very useful for future threats to keep track of new technology attacks